Pemanfaatan Teknologi Augmented Reality Untuk Memilih Model Kacamata Di Central Optikal 165 Dengan Menggunakan Metode Markerless Berbasis Android - Tarmin Abdulghani; Radityatama Mulia Sembada (Media Jurnal Informatika, 2021)
Implementation Technology Augmented Reality For Choosing Model Glasses In Central Optikal 165 With Using Markerless Method Android Based is an application android based. This application is made to make easier and attractive user when user doing selecting glasses, then application is opened front facing camera to detecting user’s face and showing 3D model object glasses.This application Implementation Glasses Augmented Reality Technology With Using Markerless Method Android Based is an application android based use UML paradigm with design Usecase Diagram, and Swimlane Diagram. While for make this application use Unity3D, and Android Studio.